The dynamics of marriage and divorce - Gustaf Bruze; Michael Svarer; Yoram Weiss (Institute for the Study of Labor (IZA), 2012)
We formulate and estimate a dynamic model of marriage, divorce, and remarriage using 27 years of panel data for the entire Danish cohort born in 1960. The marital surplus is identified from the probability of divorce, and the surplus shares of husbands and wives from their willingness to enter marriage. Education and marriage order are complements in generating gains from marriage. Educated men and women receive a larger share of the marital gains but this effect is mitigated when their proportion rises. Education stabilizes marriage and second marriages are less stable. As the cohort ages, uneducated men are the most likely to be single.
urn:nbn:de:101:1-201206146542
Keywords: J12; 330; marriage; divorce; sorting; Ehe; Scheidung; Bildungsniveau; Familienökonomik; Dänemark